(3*5-5)(5-1)=x

Simple and best practice solution for (3*5-5)(5-1)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3*5-5)(5-1)=x equation:


Simplifying
(3 * 5 + -5)(5 + -1) = x

Multiply 3 * 5
(15 + -5)(5 + -1) = x

Combine like terms: 15 + -5 = 10
(10)(5 + -1) = x

Combine like terms: 5 + -1 = 4
10(4) = x

Multiply 10 * 4
40 = x

Solving
40 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
40 + -1x = x + -1x

Combine like terms: x + -1x = 0
40 + -1x = 0

Add '-40' to each side of the equation.
40 + -40 + -1x = 0 + -40

Combine like terms: 40 + -40 = 0
0 + -1x = 0 + -40
-1x = 0 + -40

Combine like terms: 0 + -40 = -40
-1x = -40

Divide each side by '-1'.
x = 40

Simplifying
x = 40

See similar equations:

| 4p-5=18 | | -7b-5(b-4)= | | x^2-7x-7=0 | | x^2+10x+39=-3x+3 | | 3x^3-17x^2=6x | | 14n-3(nt-4)= | | x^2-3x+5=9 | | 2b^2-16b=0 | | 3x-5+x=31 | | (x^2+3x+9)(2x^3+3x-4)(4x^2+2x^2-8x)= | | 8(6x+3)+3x=x | | 3x+18=x+2 | | 25*2.3=0 | | 25*2.3= | | P(x)=x^3-7x^2+17x-15 | | 4+(7*25)20-38=x | | 25*2.3=57.5 | | 4x^2+11x+5=-4x+2 | | 3x+18=x+3 | | 13a-6(a+5)=x | | 3x^3+4-2x^4= | | 82-3*8=x | | 4x^2-27x+37=-3x+2 | | 82-3*(5-3)3=x | | (7b-3)+(b-4)=646 | | y^2+10Y+25=121 | | a^2+14a-18=0 | | -12(x-4)=-138 | | z^2+12z-25=0 | | (6x^3+7x+12)-(3x^2+8x+8)= | | -3+2x=19 | | 2z-31=9z+21 |

Equations solver categories